Ice-Candy – Man: A Tale of Partition & Its Repercussions: A Parsi Girl's Perspective on Partition and Cultural Identity (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Sidhwa’s Ice-Candy-Man (1981), chronicles the exodus of prsis to india during pre-partition era, explaining their world-view, customs, religious practices and politics. Sidhwa’s whole world in the novel is teeming with numerous happenings of surrounding day-to-day life depicting truthfully all its political, social and religious import. Sidhwa belongs to Parsi community and she takes the liberty to voice truthfully the isolation and aloofness from which her community suffers. Lenny, the daughter of a well-to-do jobholder, is the narrator of the story of the novel. Her narration starts in her fifth year an ends after hr eighth birthday. In the course of narration, she presents the panoramic views of existing social milieu. Lenny recalls her first conscious reminisential recollection of memory of her Ayah “she passes pushing my pram with the unconcern of the hindu godess she worship”. She also remembers her house on waris road in lahore and how she used to find refuge in her godmother “one-and-a-half- room abode.”In ice-candy-man, lenny leads us dwelling on interesting facts mingled as it were, with picturesque language. The main events, besides end of the second world war, india’s independence and partition of subcontinent into Pakistan and india, revolve around the ayah.